The association of physical activity with kidney function risk among adults with long working hours - Yan, Tenglong; Nabi, Subat; Liu, Xiaodong; Zeng, Bangzhao; Song, Xin; Ding, Xiaowen; Hu, Binshuo (Frontiers in Endocrinology, 2024)
Background: Long working hours are likely associated with the decreased of kidney function, while physical activity (PA) was linked to improvements in kidney function.However, whether PA can offset the negative impact of long working hours on kidney function was unclear, which is the focus of this study.A cross-sectional study was conducted. Three approaches were adopted to distinguish the association between long working hours and regular working hours.Moderate to vigorous physical activity (PA) was assessed by a structured questionnaire. eGFR and chronic kidney disease (CKD) or not were utilized to evaluate the kidney function. Linear and logistic regression analyses were conducted to assess the association between weekly working hours, PA, and kidney function.Results: A total of 18,431 adults were enrolled in this study, including 9981 males (54.2%) and 8450 females (45.8%). The average eGFR was (99.54 ± 17.55 mL/min/1.73 m 2 ). The people worked more than 40 h/wk (98.89 ± 17.06 mL/min/1.73 m 2 ) had lower eGFR compared to those worked less than 40 h/wk (99.93 ± 17.83 mL/min/1.73 m 2 ) (p < 0.05). Individuals working longer hours exhibited lower eGFR (β = -0.772, 95% CI: -1.241, -0.303, for > 40 h/wk compared to working ≤ 40 h/wk).Engagement in moderate to vigorous PA was associated with higher eGFR values (β = 1.159, 95% CI: 0.699, 1.619) compared to low PA (< 150 minutes/wk), but this association did not reach statistical significance for the prevalence of CKD.Furthermore, PA was insufficient to reverse the decline of eGFR related to prolonged working hours.Conclusions: Prolonged working hours were associated with a decline in eGFR, while PA was found to have a protective effect on kidney function. However, PA alone may not fully mitigate the negative impact of prolonged working hours on renal health. More robust measures to protect renal function should be implemented to mitigate the damage caused by prolonged working hours.